Rabies virus-like particles expressed in HEK293 cells - Fontana, Diego Sebastian (2014)
Rabies is an infectious viral disease with a mortality rate close to 100%. Currently, there is a need to generate cheaper and more immunogenic vaccines for the effective prevention of rabies, mostly in developing countries. Virus-like particles have been widely used in viral vaccine production due to their high immunogenicity and safety during the production process. Rabies virus glycoprotein is the major antigen to trigger a protective immune response and the only protein capable of generating virus neutralizing antibodies. In this study we describe the development of a recombinant stable cell line for the production of rabies virus-like particles (RV-VLPs) expressing the rabies virus glycoprotein by lentivirus-based transduction of HEK293 cells. Protein expression was analyzed by flow cytometry, fluorescence microscopy, western blot and ELISA. Particles were purified from culture supernatant and their size and morphology were studied. Furthermore, mice were immunized with RV-VLPs, formulated with adjuvant, and these particles were able to produce a specific antibody response, demonstrating that these virus-like particles present a promising rabies vaccine candidate.